International ambidexterity future research based on bibliometric analysis - Leidi Ruano-Arcos; Diana Escandón-Barbosa; Josep Rialp-Criado (Cogent Business & Management, 2024)
This research aims to improve the understanding of the scientific contributions to international ambidexterity and identify possible lines of research. We conducted a systematic literature review of 193 articles on international ambidexterity published from 2003 to 2023 that are indexed in Scopus. The publications were systematically analyzed, and scientific mapping was carried out with the VOSviewer and ATLAS TI tools. The study reveals that research in this field focuses on multinational companies from developing countries, dynamic capabilities, internationalization, innovation, and business performance. The United States, the United Kingdom, and China lead research in this area, with the most prominent journals being the International Business Review, the Thunderbird International Business Review, and the Journal of Business Research. Based on the findings, the article suggests seven categories for future research: types of ambidexterity, organizational factors, internationalization, contextual factors, effects, relationships and capabilities, innovation, and networks. We encourage academics and practitioners to contribute to this area of research and deepen our understanding of international ambidexterity.This article delves into the notion of `international ambidexterity', or a company's capacity to balance exploration and exploitation in foreign markets. The study focuses on multinational corporations from developing countries through a comprehensive examination of literature, highlighting dynamic capacities, internationalization, innovation, and company performance. According to the research, the United States, the United Kingdom, and China are the leaders in this sector, with magazines such as the International Business Review and the Journal of Business Research playing important roles. Future study should focus on nine areas, including ambidexterity kinds, organizational characteristics, and environmental impacts, according to the findings. The paper urges researchers and practitioners to contribute to the changing knowledge of international ambidexterity, so encouraging additional research in this dynamic and essential field.The dedication of the ECGESA research group to understanding social and economic phenomena is consistent with the larger purpose of contributing to human, social, and economic development. Their multidisciplinary approach, which included scholars from other faculties, connects with the discussion of `international ambidexterity'. Both emphasis on macro and micro dynamics within varied contexts demonstrates a similar commitment to solving difficult challenges. The research described in the abstract, which emphasizes the relevance of dynamic capacities, internationalization, innovation, and firm performance in multinational enterprises from developing countries, is consistent with ECGESA's mission of understanding economic and organizational dynamics. The ECGESA group's collaborative attitude and search of answers to greater social concerns resonates with the appeal for scholars and practitioners to contribute to understanding international ambidexterity. Both highlight the need of multidisciplinary collaboration and ongoing investigation to enhance knowledge in their respective domains and contribute to the larger landscape of research and development.
Keywords: 650; MNEs; exploration international; exploitation international; ambidexterity; literature review